Evaluating Alternatives to GDP as Measures of Social Welfare/Progress - Jeroen van den Bergh; Miklós Antal (WWWforEurope, 2014)
Proposed alternatives to GDP as a measure of social welfare or human progress are briefly evaluated. Four main categories are considered, namely ISEW and GPI based on corrections of GDP, sustainable or green(ed) GDP, genuine savings/investments and composite indexes. All these alternatives turn out to suffer from various shortcomings. Nevertheless, several of them represent a considerable improvement over GDP information in approximating social welfare. This gives support to the idea that we should not wait to give less importance and attention to GDP (per capita) information in public decision-making until a perfect alternative indicator is available.
Keywords: D60; E01; O11; 330; Composite indicators; economic growth; externalities; genuine savings; green GDP; happiness; informal sector; information failure; ISEW; status goods; sustainable income